2019
DOI: 10.3389/fpsyg.2019.01615
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Performance in Sex, Sport, and Stage: Identifying Common Ground

Abstract: Anxiety has long been associated with diminished performance within a number of domains involving evaluative interpersonal interactions, including Sex, Sport, and Stage. Here, we pose three questions: (1) how do these disparate fields approach and understand anxiety and performance; (2) how does the understanding of the issue within one field offer insight to another field; and (3) how could each field benefit from the ideas and strategies used by the others. We begin with a short review of models of anxiety/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 171 publications
(250 reference statements)
2
41
0
Order By: Relevance
“…Moreover, greater anxiety/depression predicted lower relationship satisfaction and sexual satisfaction. These findings align with prior research demonstrating that anxiety and depression may increase the individual's cognitive distraction or negative affect [66,67], both of which can shift attention away from sexual behaviors or partner cues and onto competing, non-erotic stimuli [41,[68][69][70].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, greater anxiety/depression predicted lower relationship satisfaction and sexual satisfaction. These findings align with prior research demonstrating that anxiety and depression may increase the individual's cognitive distraction or negative affect [66,67], both of which can shift attention away from sexual behaviors or partner cues and onto competing, non-erotic stimuli [41,[68][69][70].…”
Section: Discussionsupporting
confidence: 88%
“…We further asked (4) whether pornography use during masturbation was related to the woman's sexual and overall relationship satisfaction with her partner. As we assessed these relationships, we (5) controlled for the independent effects of a number of covariates known for affecting sexual response, including anxiety/depression [39][40][41], menopausal status [42], and a number of health and demographic factors, including ongoing medical issues, age [43], and education level [44,45].…”
Section: Aims Of the Current Studymentioning
confidence: 99%
“…These interpersonal aspects are known to provoke anxiety which in turn may affect performance and may eventually lead to avoidance. Examples of anxiety affecting performance have been well documented in all three fields (See Rowland and van Lankveld [ 16 ] for examples, or search online for “famous performers or celebs with stage fright” or “famous athletes with performance anxiety”).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, negative body image may affect orgasmic capacity primarily through an anxiety-evoking evaluative process that operates primarily during partnered sex. 46 Thus, negative body image could have different effects on orgasmic response, depending on whether masturbation or partnered sex is involved. 11 To date, several studies have indicated that masturbation tends to be associated with a more positive body image, the idea being that women who masturbate are more able to associate sexual pleasure with their bodily responses and, in doing so, develop greater satisfaction with their bodies.…”
Section: Introductionmentioning
confidence: 99%
“… 49 , 50 On the one hand, the distress and spectatoring/distraction related to negative body image 51 , 52 can interfere with emotional closeness, leading to diminished intimacy and therefore to diminished relationship quality. 45 , 46 On the other hand, high relationship satisfaction may help protect against the negative effects of negative body image on sexual functioning. 43 , 44 , 51 , 52 Furthermore, positive body image and self-esteem appear to buffer the negative effects of a conflicted relationship.…”
Section: Introductionmentioning
confidence: 99%